Effective separation of aromatic hydrocarbons by pyridine‐based deep eutectic solvents. (9th September 2019) - Feng, Shanhua; Sun, Jianjun; Ren, Zhongqi; Zhou, Zhiyong; Zhang, Fan; Liu, Wei
Abstract: Many promising qualities of deep‐eutectic solvents made them suitable solvents in separation process. In this work, the pyridine‐based deep eutectic solvents were designed and synthesized with N‐ ethylpyridinium bromide and two HBDs ( N ‐formyl morpholine and levulinic acid). Two ternary systems, benzene + cyclohexane + DES and toluene + n ‐heptane + DES, were studied by the liquid‐liquid extraction. The effect of different HBDs, extraction time, volume ratio of DES to system solution, and the initial concentration of aromatic were studied. The DES with N ‐formyl morpholine showed better separation performance than that with levulinic acid. The liquid‐liquid extraction equilibrium could be obtained in 10 minutes. The volume ratio of DES to system solution was set as 1:1. Both DESs showed their best separation performance at low temperatures (20°C) and low aromatic concentration system. For the benzene + cyclohexane system, the distribution coefficient of benzene was 1.733 and the selectivity was 23.8 at 20°C. For the toluene + n ‐heptane system, the distribution coefficient of toluene was 0.853 and the selectivity was 40.7. Tie‐lines for two ternary systems were obtained, and the Othmer‐Tobias correlation was used to check the reliability of the obtained liquid‐liquid extraction experimental data. The experimental LLE data were correlated using the NRTL model and the calculated data correlated significantly with the experimental data. Abstract : Tie‐lines for two ternary systems at 20°C and 40°C.